Molecular surface interaction modeling of Poly(vinyl pyrrolidone) on Multi-walled carbon nanotubes - Veintimilla Carrión, Keiko Sahori (2023)
In recent years, the potential of multi-walled carbon nanotubes (MWCNT) for use in biomedical applications has been highlighted due to their unique chemical and physical properties. However, the development of new MWCNT devices faces significant challenges, such as biocompatibility, dispersion capability, and dissolution in polar solvents. One of the most commonly used strategies is coating the carbon nanotubes with molecules capable of interacting with them and providing properties suitable for a biological environment. Polyvinylpyrrolidone (PVP) is a biocompatible polymer that exhibits complex affinity for hydrophilic and hydrophobic drugs, making it an ideal candidate for coating MWCNTs. Therefore, in this thesis project, a study of the interaction between PVP and carbon nanotube surfaces was carried out to determine PVP behavior on the surface through computational tools. Two models of carbon nanotubes were developed to understand the influence of the tubular structure and multiple layers on interaction with PVP polymers. The study identified a wrapping phenomenon and a closer distance to PVP with the SWCNT model than the layer model. The article concludes that the amount of PVP polymer used with CNT should be estimated based on the intended application, as the properties of the nanotube and polymer may be affected depending on the amount. This study highlights the potential use of PVP as a coating material for MWCNTs and provides information on the interaction between PVP and CNT surfaces, which could contribute to the development of safer and more effective biomedical devices.